(untitled) (Nordic Journal of African Studies, 2005)
This paper examines an indigene-settler divide in the Cameroonian urban social space as an emanation of the land question, and hinges on the role which modernisation has played. The paper argues that modernization, despite its weak legal framework in Douala, has managed to sustain a fragmented urban social co-existence among stakeholders from the two groups. The paper finds that within the context of such an indigene-settler dichotomy, social coexistence is being fragmented by rising animosity as the government and the various groups have resorted to a politicisation of the land question. What ensues has been a withering of meritocratic and democratic values in this modern space. The paper concludes that this divide over land and the problems associated with its politicisation poses a challenge to a sustainable urban governance project in Douala. The essay recommends a government and community partnership of the urban stakeholders within a framework of dialogue if these anti-modern processes are to be overcome.